The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1128/iai.72.9.5027-5030.2004
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Preventive Sulfadoxine-Pyrimethamine Treatment of Primigravidae Reduces Levels of Plasma Immunoglobulin G, Which Protects against Pregnancy-Associated Plasmodium falciparum Malaria

Abstract: Pregnancy-associated malaria (PAM) is an important cause of maternal and neonatal suffering. It is causedby Plasmodium falciparum capable of inhabiting the placenta through expression of particular variant surface antigens (VSA) with affinity for proteoglycans such as chondroitin sulfate A. Protective immunity to PAM develops following exposure to parasites inhabiting the placenta, and primigravidae are therefore particularly susceptible to PAM. The adverse consequences of PAM in primigravidae are preventable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
26
7
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 24 publications
6
26
7
3
Order By: Relevance
“…This is the first study to report the influence of IPT on Ab levels to the FV2 in longitudinal cohort of primigravidae. Similar to previous studies that measured Abs to the surface of CSA-binding IE, 21 reduced exposure to malaria in primigravidae resulted in reduced Ab acquisition to VAR2CSA (Figures 1-3). After the first dose of SP, a general decline in Abs to VAR2CSA in primigravidae was observed, suggesting that only short-lived plasma cells had been produced.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This is the first study to report the influence of IPT on Ab levels to the FV2 in longitudinal cohort of primigravidae. Similar to previous studies that measured Abs to the surface of CSA-binding IE, 21 reduced exposure to malaria in primigravidae resulted in reduced Ab acquisition to VAR2CSA (Figures 1-3). After the first dose of SP, a general decline in Abs to VAR2CSA in primigravidae was observed, suggesting that only short-lived plasma cells had been produced.…”
Section: Discussionsupporting
confidence: 74%
“…19 Unfortunately, the use of IPT and ITN remains low throughout Africa. 20 Studies have reported IPT and/or ITN may reduce the Ab response to placental-binding IE or VAR2CSA in primigravidae and multigravidae, [21][22][23][24][25] but many questions remain. In particular, a limited understanding exists about how these interventions affect the quality and specificity of the anti-VAR2CSA Ab response acquired by primigravidae and if multigravidae, who acquired immunity to PM in previous pregnancies, maintain their immunity.…”
Section: Introductionmentioning
confidence: 99%
“…19 In defense of limited S/P use during pregnancy, plasma IgG, which mediates protection against placental malaria, was reportedly unaffected in primigravidae given single-dose S/P, but was reduced 2-8-fold in those given multiple doses. 20 In rural Burkina Faso, where 23% of primigravid women were parasitemic at delivery and 24% of their newborns were LBW, > 1 IPTp dose of S/P was associated with fewer parasitemias, but 2-3 doses were associated with significantly fewer LBW deliveries, and birth weights that increased in direct proportion to IPTp dosing. 21 Irrespective of parity, single-dose S/P in pregnant, human immunodeficiency virus-positive, Zambian women was associated with poorer outcomes than two doses for both mother and newborn, but three or more doses yielded no further benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Cet antigène fait l'objet de plusieurs études pour une meilleure compréhension et une amélioration de la prise en charge du paludisme au cours de la grossesse. En effet, les femmes ayant présenté une grossesse impaludée développent des anticorps spécifiques anti-VAR2CSA qui seraient associés à une meilleure protection contre le paludisme au cours des grossesses ultérieures [8,30,31]. L'antigène VAR2CSA connaît un polymorphisme.…”
unclassified
“…Toutefois, il existe peu de données immunologiques, concernant l'influence du TPI sur l'acquisition d'anticorps antipalustres chez la femme enceinte [30,31].…”
unclassified